Strategi Menjemput Sukses Menuju Kampus Keren - Maisarah, Maisarah (Ameena Journal, 2023)
The research aims are as follows: 1) To understand the school's strategies in getting students admitted to public universities through the SNMPTN/SBMPTN (UTBK) pathways at MAN 1 West Aceh, 2) To identify the inhibiting factors in implementing the school's strategies to achieve student admissions to public universities through the SNMPTN/SBMPTN (UTBK) pathways at MAN 1 West Aceh, and 3) To assess the impact of these strategies on student admissions to public universities through the SNMPTN/SBMPTN (UTBK) pathways at MAN 1 West Aceh. The research employs a field research methodology, which involves collecting data directly from the field. Data is gathered through observations and interviews conducted with respondents aligned with the research objectives, as well as through document analysis. The research findings indicate the following: 1) The strategies employed by the school to ensure student admissions to public universities through the SNMPTN/SBMPTN (UTBK) pathways at MAN 1 West Aceh include improving semester grades, enhancing student motivation and learning enthusiasm, honing student skills, collaborating with education-focused entities, and introducing additional after-school learning sessions. 2) The inhibiting factors affecting the implementation of these strategies for student admissions to public universities through the SNMPTN pathways at MAN 1 West Aceh encompass a lack of knowledge about selected majors in the SNMPTN system, challenges related to inputting accurate grades, as well as issues concerning students' motivation and enthusiasm to pursue higher education at public universities. The solutions involve fostering cooperative efforts among teachers to optimize the teaching process, encouraging the school community's commitment to maintain accurate student assessments, and showcasing the dedication of teachers to successfully guide students to higher education. Additional steps include prioritizing student registration for achieving scholarships like "bidik misi" and other forms of financial aid. 3) The impacts experienced by MAN 1 West Aceh due to students succeeding through the SNMPTN pathways include enhancing the school's image and reputation in the eyes of the community, boosting the motivation of potential new students to enroll, elevating the school's accreditation, and serving as an indicator of the performance of both teachers and the school.